Genomic signatures of evolution in Nautilus—An endangered living fossil. Issue 21 (7th October 2017) - Combosch, David J.; Lemer, Sarah; Ward, Peter D.; Landman, Neil H.; Giribet, Gonzalo
Abstract: Living fossils are survivors of previously more diverse lineages that originated millions of years ago and persisted with little morphological change. Therefore, living fossils are model organisms to study both long‐term and ongoing adaptation and speciation processes. However, many aspects of living fossil evolution and their persistence in the modern world remain unclear. Here, we investigate three major aspects of the evolutionary history of living fossils: cryptic speciation, population genetics and effective population sizes, using members of the genera Nautilus and Allonautilus as classic examples of true living fossils. For this, we analysed genomewide ddRAD‐Seq data for all six currently recognized nautiloid species throughout their distribution range. Our analyses identified three major allopatric Nautilus clades: a South Pacific clade, subdivided into three subclades with no signs of admixture between them; a Coral Sea clade, consisting of two genetically distinct populations with significant admixture; and a widespread Indo‐Pacific clade, devoid of significant genetic substructure. Within these major clades, we detected five Nautilus groups, which likely correspond to five distinct species. With the exception of Nautilus macromphalus, all previously described species are at odds with genomewide data, testifying to the prevalence of cryptic species among living fossils. Detailed F ST analyses further revealed significant genome‐wide and locus‐specific signatures of selection between species and differentiated populations, which is demonstrated here for the first time in a living fossil. Finally, approximate Bayesian computation (ABC) simulations suggest large effective population sizes, which may explain the low levels of population differentiation commonly observed in living fossils.